Conception of the professionals of psychosocial care center on public policies of mental health (Research, Society and Development, 2020)
This study aimed to verify the conception of professionals of the CAPS on the Public Policies of Mental Health and its implantation. It was a qualitative, exploratory, descriptive study, with Content Analysis framework. 27 professionals from 9 CAPS linked to São Paulo Municipal Government, in all regions, were interviewed. Most participants highlighted the gap between what is advocated in legislation and the practice in their services. Inequalities between the regions of the city, mismatch between proposals from the municipal and state spheres, peculiarities of administration by Social Health Organizations and the prevalence of asylum logic in health and intersectoral networks were also observed. Despite the advances in the Psychiatric Reform, there is a need for confrontation and political investment to effectively implement Deinstitutionalization.